2001
DOI: 10.1136/thorax.56.8.613
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous female sex steroid hormones and risk of asthma and asthma-like symptoms: a cross sectional study of the general population

Abstract: Background-Recent evidence suggests a role for hormonal factors in the aetiology of asthma. Methods-Data from a large study of women selected from the general population were used to relate treatment with oral hormonal contraceptives (OCP) and postmenopausal hormone replacement therapy (HRT) to the following asthma indicators: self-reported asthma, wheezing, cough at exertion, and use of medication for asthma. The study sample comprised 1536 premenopausal and 3016 postmenopausal women who participated in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 20 publications
4
56
1
1
Order By: Relevance
“…A few studies have addressed this issue and found a decreased risk of developing asthma with increased length of OC use [13•], no effect [14], and an increased risk of current wheeze with OC use [9].…”
Section: The Role Of Sex Hormones In Asthma Susceptibility and Severitymentioning
confidence: 99%
“…A few studies have addressed this issue and found a decreased risk of developing asthma with increased length of OC use [13•], no effect [14], and an increased risk of current wheeze with OC use [9].…”
Section: The Role Of Sex Hormones In Asthma Susceptibility and Severitymentioning
confidence: 99%
“…Some studies suggest that asthma incidence is significantly higher in postmenopausal women being on hormone replacement therapy (HRT), than in those who never used it (54). Moreover, it has been shown the association of maternal use of oral contraceptives before birth with a higher risk of atopic diseases (asthma, allergic rhinitis and atopic egzema) in the offspring compared with children of mothers who had never taken hormonal pills (55).…”
Section: Phytoestrogens Gender and Allergic Responsementioning
confidence: 99%
“…41 In a study by Lange, no relationship was found between use of oral contraceptives and asthma. 42 Erkoçoğlu et al 45 found in a survey on 487 women by means of a questionnaire that 196 (40.2%) reported using oral contraceptives. This use was associated with higher risk of current wheezing among adolescents and young adults, but only among those who had taken the oral contraceptives recently during the previous year.…”
Section: Use Of Hormone Contraceptives and Asthmamentioning
confidence: 99%